Pengaruh Pelatihan Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan pada PT. Kreasindo Jaya Tama Sukses Bekasi - Sulistyani, Geddy; Rismayadi, Budi; Pertiwi, Wike (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This research aims to find out about the influence of training and work environment on employee performance at PT. Kreasindo Jaya Tama Sukses Bekasi. The method used in this researchthe is the quantitative method. This research was conducted at PT. Kreasindo Jaya Tama Sukses. The sample collection technique uses all employees of PT. Kreasindo Jaya Tama Sukses with a total of 105 employees. To determine the total of samples used, use the slovin formula with a margin error of 10% and there were result 52 employees who were used as respondents. The analysis model used in this research is multiple linear regression analysis using the f-test and t-test with a significance level of 5%. The research results show that there is a partial influence between job training on employee performance and the t table value (3,739 > 1,676 atay thitung > ttabel). Meanwhile, there is a partial influence of the work environment on employee performance with t table (2,329 > 1,676).